Adrenal and hepatic aspergillosis in an immunocompetent patient. Issue 6 (June 2015) - Chen, Liyu; Liu, Yanbin; Wang, Weiya; Liu, Kai
Abstract: Invasive aspergillosis, an infection most frequently induced by Aspergillus fumigatus and Aspergillus flavus, typically occurs in immunocompromised patients and is usually transmitted through inhalation of Aspergillus spores. As the lungs are by far the most common site involved in invasive aspergillosis and invasive aspergillosis in immunocompetent hosts is very rare, there have been a few case reports of extra-pulmonary, disseminated invasive aspergillosis in immunocompetent persons. Herein, we report a case of an adult, male, immunocompetent patient with disseminated invasive aspergillosis that successively spread from the right adrenal gland to the left hepatic lobe. The patient was successfully treated through surgical excisions of his adrenal and hepatic masses followed by voriconazole therapy. To our knowledge, this is the first case report of invasive aspergillosis affecting the adrenal glands.